Linear encoder based low frequency inertial sensor. Issue 3 (1st October 2016) - Hellegouarch, Sylvain; Fueyo Roza, Lionel; Artoos, Kurt; Lambert, Pierre; Collette, Christophe
ABSTRACT: In this article, we present a novel concept of inertial sensor, based on a linear encoder. Compared to other interferometric sensors, the encoder is much more easy to mount, and the calibration more stable. A prototype has been built and validated experimentally by comparison with a commercial seismometer. It has a resolution of about 10 pm/√Hz. In order to further improve the resolution, two concepts of mechanical amplifiers have been studied and compared. One of them is shown to be extremely promising, provided that the amplifier does not stiffen the sensor.